Sunardi KONSEP DASAR PERTUNJUKAN WAYANG SINEMA LAKON DEWA RUCI - Sunardi; I Nyoman Murtana; Sudarsono (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2020)
This paper aims to describe the basic concepts of wayang cinema performance Dewa Ruci play as an alternativeto the development of Indonesian puppets. Wayang Cinema is an innovative wayang performance in awide-screen film. The problems examined are: (1) what lies behind the creation of wayang cinema Dewa Ruciplay; and (2) what is the basic concept and structure of wayang cinema performance Dewa Ruci play. Thestudy was conducted by applying the methods of art creation, namely exploration, design, creation, andpresentation. The results showed that: first, the creation of wayang cinema Dewa Ruci play was motivated bythe decreasing of younger generation’s interest in wayang. The wayang life is marginalized, responding to thechallenges of the era namely the industrial era 4.0., And as a continuation of puppet show experiments.Secondly, the basic concept of wayang cinema Dewa Ruci play is to emphasize the work on the play and thepresence of the song as a driver of plot, characterization, and strengthening the atmosphere, in addition tobeing packaged in the form of widescreen films. Third, the structure of wayang cinema Dewa Ruci playemphasizes the portrayal of the Bima figure in achieving tirta pawitra with a new style.